Remarkable diversity of the genus Endonura Cassagnau, 1979 (Collembola: Neanuridae: Neanurinae) in the Caucasus - Smolis, Adrian; Kuznetsova, Nataliya (Zootaxa, 2016)
Endonura alticola (Stach, 1951) comb. nov. is redescribed based on the type material and seven new species of the genus Endonura are described from the various parts of the Caucasus. E. paracantabrica sp. nov. can be recognized by the number of chaetae (L+So) on head and a fusion of tubercles Di and De on the first thoracic segment. Specific traits of E. aibgai sp. nov. include small body size, low number of chaetae (L+So) on head, nonogival labrum, dentate claws, and long tibiotarsal chaetae B4 and B5. E. diminutichaeta sp. nov. is characterized by an unusually short chaeta Di1on abdomen IV. E. dobrolyubovae sp. nov. can be distinguished from its congeners by notably long chaeta Ocp on head and the presence of male ventral organ. The absence of chaetae E and O on head, ogival labrum, cryptopygy and dentate claws are typical of E. cryptopyga sp. nov. E. ossetica sp. nov. is most easily recognized by an unusual shape of tubercle Af on head connected with chaetae D and E. Main characteristics of E. kremenitsai sp. nov. include the presence of chaeta E and five chaetae Dl on head. A key to all known species of the genus including the above outlined taxa is given. General remarks on distribution and possible historical biogeography of the genus are also provided.